THU0582 Prognostic Factors of Macrophage Activation Syndrome in Adults: Analysis of 40 Cases in 2 Tertiary Referral Centers. (15th July 2016) - Ruscitti, P.; Ciccia, F.; Cipriani, P.; Guggino, G.; Liakouli, V.; Carubbi, F.; Berardicurti, O.; Di Benedetto, P.; Triolo, G.; Giacomelli, R.
Abstract : Background: Macrophage activation syndrome (MAS) is a rare, life-threatening disease in which early diagnosis and aggressive therapeutic strategy may improve the outcome [1]. Due to its rarity, epidemiologic data are still lacking. Hyperferritinemia is frequently associated with MAS and might modulate the cytokines storm the latter contributing to the development of multi-organ failure [2]. Objectives: In the current study, we aimed to investigate clinical data, treatments, and outcome of adult MAS patients secondary to autoimmune rheumatic disease. Methods: We retrospectively investigated clinical data, treatments, and outcome of 40 adult MAS patients secondary to autoimmune rheumatic disease. For all the MAS patients, the following clinical characteristics were recorded: age, gender, values of serum ferritin, erythsedimentation rate (ESR) and C-reactive protein (CRP), treatments, concomitant comorbidities, time of observation and outcome. Furthermore, we evaluated the correlations among these clinical features and MAS-associated death. Results: Forty consecutive MAS patients, 15 men (37.5%) and 25 women (62.5%), whose mean age at diagnosis was 48.20±14.10 (mean±SD) were enrolled. Thirty out of 40 enrolled patients reported an history of adult onset Still's disease (AOSD) (75%), 8 patients an history of systemic lupus erythematosus (20%), 1 patient an history of systemic sclerosis (2.5%), and 1 an history of ankilosing spondylitis (2.5%). Twenty-four out of enrolled patients (60%) did not show any comorbidity, and MAS was diagnosed during an AOSD flare. A severe infections was associated with MAS in the other patients. The laboratory data (mean±SD) reported a strong increase of inflammatory markers: i. serum ferritin 6842.70±7569.70 ng/mL; ii. ESR 63.87±30.19 mm/hr; iii. CRP 51.59±46.92. All the patients were treated with pulsed high dosage of methylprednisolone (1000 mg/daily for a maximum of 6 cycles) and 16 patients (16, 40%) received a combination therapy with: cyclosporin (13, 32.5%); methotrexate (6, 15%); intravenous immunoglobulin therapy (3, 7.5%); anakinra (3, 7.5%); tocilizumab (1, 2.5%). MAS-associated death occurred in 17 patients (42.5%). By using Cox regression proportional hazard model of survival of enrolled MAS patients, we observed that: older age [p=0.017, EXP(B): 1.305, 95%CI: 1.006–1.365], increased serum ferritin levels [p=0.001, EXP(B): 1.776, 95%CI: 1.030–2.728], increased CRP levels [p=0.029, EXP(B): 1.511, 95CI%: 1.021–1.651], higher number of comorbidities [p=0.01, EXP(B): 1.751, 95%CI: 1.142–2.2686], and the use biologics [p=0.015, EXP(B): 2.915, 95%CI: 1.233–6892] were significantly associated with MAS-associated death. Conclusions: Adult MAS is still associated with higher mortality rate. Some clinical features at diagnosis, such as older age, increased serum ferritin and CRP levels and higher number of comorbiditis, may be associated with MAS-associated death. References: Ramos-Casals M et al, Adult haemophagocytic syndrome. Lancet 2014; 383: 1503–16. Rosário C et al, The hyperferritinemic syndrome: macrophage activation syndrome, Still's disease, septic shock and catastrophic antiphospholipid syndrome, BMC Med 11, 2013, 185. Disclosure of Interest: None declared